Greece's new agreement with Europe: Is this time different? - Paul B. Kazarian; Theodore Pelagidis (Intereconomics, 2015)
The correct understanding of Greece's debt can only be obtained by using international accrual accounting standards rather than the cash-basis future face value defi nition. Changing the terms of debt changes the value of the debt in Greek governmental fi nancial statements correctly prepared according to internationally promulgated accounting and statistical rules. This article provides some detailed answers on the rules for measuring debt and debt relief and the application to Greece.
Keywords: 330; Öffentliche Schulden; Schuldenkrise; Schuldenmanagement; Griechenland